Orbital period variations in HT Cas: evidence for additional angular momentum loss and a High-eccentricity Giant Planet - Han, Z. T. (2023)
We present a timing study of the short-period eclipsing cataclysmic variable (CV) HT Cas. Based on new eclipse times derived from our photometric monitoring and archival optical data, combined with historical timings, spanning ∼42 yr, we detect a secular decrease in the orbital period at a rate of ￼ and a cyclic period wiggle with an amplitude of 79.3 s and a period of 30.28 yr. We find that neither gravitational radiation nor magnetic braking can explain the observed decrease rate, suggesting the presence of additional angular momentum loss (AML). The empirical consequential AML (eCAML) model developed by Schreiber et al. can well match the observed orbital decay in HT Cas, and the physical mechanism for eCAML is most likely attributable to the frictional AML following nova eruptions. As for the cyclic variation, the best explanation is the influence of an unseen companion in orbit around the binary. The derived orbital parameters reveal that the hypothetical third body could be a giant planet with mass of M3 ≃ 14MJup that is moving on a highly eccentric orbit (e = 0.82). Taken together the results of the present study suggest that HT Cas is a unique triple system containing a high-eccentricity giant planet and it has the potential to become an ideal laboratory in which to test models of CV evolution.